Potential Biomarkers for Treatment Response to the BCL-2 Inhibitor Venetoclax: State of the Art and Future Directions - Salah, Haneen T. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Apoptosis dysergulation is vital to oncogenesis. Efforts to mitigate this cancer hallmark have been ongoing for decades, focused mostly on inhibiting BCL-2, a key anti-apoptosis effector. The approval of venetoclax, a selective BCL-2 inhibitor, for clinical use has been a turning point in the field of oncology. While resulting in impressive improvement in objective outcomes, particularly for patients with chronic lymphocytic leukemia/small lymphocytic lymphoma and acute myeloid leukemia, the use of venetoclax has exposed a variety of resistance mechanisms to BCL-2 inhibition. As the field continues to move forward, improved understanding of such mechanisms and the potential biomarkers that could be harnessed to optimize patient selection for therapies that include venetoclax and next-generation BCL-2 inhibitors are gaining increased importance. ABSTRACT: Intrinsic apoptotic pathway dysregulation plays an essential role in all cancers, particularly hematologic malignancies. This role has led to the development of multiple therapeutic agents targeting this pathway. Venetoclax is a selective BCL-2 inhibitor that has been approved for the treatment of chronic lymphoid leukemia and acute myeloid leukemia. Given the reported resistance to venetoclax, understanding the mechanisms of resistance and the potential biomarkers of response is crucial to ensure optimal drug usage and improved patient outcomes. Mechanisms of resistance to venetoclax include alterations involving the BH3-binding groove, BCL2 gene mutations affecting venetoclax binding, and activation of alternative anti-apoptotic pathways. Moreover, various potential genetic biomarkers of venetoclax resistance have been proposed, including chromosome 17p deletion, trisomy 12, and TP53 loss or mutation. This manuscript provides an overview of biomarkers that could predict treatment response to venetoclax.